Upaya Peningkatan Pengetahuan, Sikap dan Perilaku dengan Kejadian Muntaber melalui Perilaku Hidup Bersih dan Sehat: Efforts to Increase Knowledge, Attitudes and Behavior with Vomiting and Defecation Events through Clean and Healthy Behavior - Richa Noprianty; Ika Kurnia Sukmawati; Shinta Ika Shandi; Vivop Marti Lengga; Reza Qrista Adianti (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2023)
Clean and healthy living behavior in the household is one of the efforts so that the community is in a clean and healthy environment so that it can reduce the incidence of infectious and non-communicable diseases. This is in accordance with one of the themes of the sustainable development goals, namely a healthy and prosperous life. One of the diseases that often arise in the community is diarrhea. Data from the Cimanggung Community Health Center showed that 9.59% of people with vomiting and defecation occurred in Sindanggalih Village. The implementation of community service was carried out in August 2022 by lecturers and students of Bhakti Kencana University. The target of the activity is RW 1-10 cadres, totalling 37 people. Providing health promotion about vomiting and defecation, drug self-medication and Oral rehydration solution demonstration. The community was given a pre-test and post-test in the form of a knowledge, attitude and action questionnaire to measure the achievement of activities. The results show that the average pre-test knowledge is 8.13 and the post-test average is 8.83; the average attitude of the pre-test was 16.32 and the post-test was 16.70 and the mean of the pre-test was 16.35 and the post-test was 16.97. This shows that there is an increase in knowledge of 0.7, attitude of 0.38 and action of 0.62.